Strongyloides stercoralis age-1: A Potential Regulator of Infective Larval Development in a Parasitic Nematode - Stoltzfus, Jonathan D.; Massey, Jr, Holman C.; Nolan, Thomas J.; Griffith, Sandra D.; Lok, James B. (PLOS ONE, 2012)
Infective third-stage larvae (L3i) of the human parasite Strongyloides stercoralis share many morphological, developmental, and behavioral attributes with Caenorhabditis elegans dauer larvae. The ‘dauer hypothesis’ predicts that the same molecular genetic mechanisms control both dauer larval development in C. elegans and L3i morphogenesis in S. stercoralis. In C. elegans, the phosphatidylinositol-3 (PI3) kinase catalytic subunit AGE-1 functions in the insulin/IGF-1 signaling (IIS) pathway to regulate formation of dauer larvae. Here we identify and characterize Ss-age-1, the S. stercoralis homolog of the gene encoding C. elegans AGE-1. Our analysis of the Ss-age-1 genomic region revealed three exons encoding a predicted protein of 1,209 amino acids, which clustered with C. elegans AGE-1 in phylogenetic analysis. We examined temporal patterns of expression in the S. stercoralis life cycle by reverse transcription quantitative PCR and observed low levels of Ss-age-1 transcripts in all stages. To compare anatomical patterns of expression between the two species, we used Ss-age-1 or Ce-age-1 promoter::enhanced green fluorescent protein reporter constructs expressed in transgenic animals for each species. We observed conservation of expression in amphidial neurons, which play a critical role in developmental regulation of both dauer larvae and L3i. Application of the PI3 kinase inhibitor LY294002 suppressed L3i in vitro activation in a dose-dependent fashion, with 100 µM resulting in a 90% decrease (odds ratio: 0.10, 95% confidence interval: 0.08–0.13) in the odds of resumption of feeding for treated L3i in comparison to the control. Together, these data support the hypothesis that Ss-age-1 regulates the development of S. stercoralis L3i via an IIS pathway in a manner similar to that observed in C. elegans dauer larvae. Understanding the mechanisms by which infective larvae are formed and activated may lead to novel control measures and treatments for strongyloidiasis and other soil-transmitted helminthiases.